A reflective account of using child‐led interviews as a means to promote discussions about reading. (12th December 2021) - Webber, Charlotte; Wilkinson, Katherine; Andries, Valentina; McGeown, Sarah
Abstract: This article provides a reflective account of the participatory methodology employed in the Growing up a Reader research study. The aim of the Growing up a Reader study was to explore children's (age 9–11) perceptions of a 'reader' and their reasons for reading different text types. This involved training 12 primary school children as student interviewers. Students were interviewed by the adult research team and then interviewed peers themselves ( n  = 21). For the purpose of this reflection, a data‐driven inductive thematic analysis of the interviews was conducted and comparisons were drawn between those led by children and those led by adults. Child‐led interviews were more likely to lead to natural discussions about reading as students engaged in the co‐creation of knowledge surrounding their shared reading experiences. Child‐led interviews also featured creative communication styles and reflexive use of language to understand each other's reading experiences. Reflections upon child‐led interviews as a tool for deepening understanding of children's literary experiences are made in order to provide methodological insights relevant for both researchers and practitioners seeking to use participatory methods to collaborate with children. Limitations regarding training and support, and ethical and epistemological considerations regarding adult input are also discussed.